Highly efficient conversion of methane to formic acid under mild conditions at ZSM-5-confined Fe-sites. (April 2021) - Zhu, Kaixin; Liang, Suxia; Cui, Xiaoju; Huang, Rui; Wan, Ningbo; Hua, Lei; Li, Haiyang; Chen, Hongyu; Zhao, Zhenchao; Hou, Guangjin; Li, Mingrun; Jiang, Qike; et al.
Abstract: Production of value-added chemicals from oriented methane conversion under mild conditions is of great significance for utilization of the energy resources, which, however, remains a great challenge due to its difficulty in the selective activation of C–H bond. Herein, we report a highly selective and efficient methane conversion to formic acid on atomically dispersed Fe sites confined in the nano-channels of ZSM-5. The turnover frequency for producing C1 liquid oxygenates reaches 84, 200 h −1 with a high selectivity of 91% to formic acid at 80 °C, which outperforms all previously reported catalysts. Electron paramagnetic resonance analysis and density functional theory calculations demonstrate that the ZSM-5-confined Fe-O active centers can facilely dissociate the C–H bonds and catalyze successive oxidation of methane to formic acid via free radical mechanisms under mild conditions. This study opens a new path of engineering the microenvironment of confined Fe sites within nano-channels toward highly selective methane conversion with low energy input. Graphical Abstract: Atomically-dispersed Fe sites confined within nano-channels of ZSM-5 enable highly efficient methane oxidation to formic acid, reaching a high selectivity of 91% and unprecedented TOF of 84, 200 h −1 via free radical mechanisms over the active oxygen species generated on both mononuclear and binuclear Fe sites. ga1 Highlights: Highly efficient CH4 oxidation to HCOOH is achieved at ZSM-5 confined Fe under mild conditions. The optimized Fe/ZSM-5(66) delivers HCOOH selectivity of 91% and TOF of 84, 200 h −1 . Both mononuclear and binuclear Fe-O sites facilitate C–H bond cleavage of methane. Successive methane oxidation to HCOOH goes through free radical pathways.